Severe Ischemic Stroke due to Progression of Cervical Carotid Artery Dissection - Inoue Nobuhiro; Kawano Takayuki; Kitajima Mika; Sueyoshi Hiroyuki; Kobayashi Osamu; Kakizoe Yusuke; Ikeda Tomomi; Ueno Yukiko; Fukuda Shingo; Iwata Michiya; Fuyuta Shuhei (Journal of Neurological Research And Therapy, 2017)
Spontaneous dissection of the cervical segment of the internal carotid artery (CS-ICA) is uncommon but not rare. A 43-year-old man suddenly developed complete right hemiparesis with motor aphasia. 3 weeks after the initial symptom onset. Magnetic resonance imaging showed enlargement of an intramural hematoma at the cervical carotid artery; it severely compressed and completely occluded the arterial lumen. Diffuse ischemia was observed in the area of the left middle cerebral artery (MCA) immediately after onset and he underwent emergency left superficial temporal artery-MCA double bypass within 6 hours. There was no fatal deterioration and his neurological deficit was resolved. We discuss our treatment of spontaneous dissection of the CS-ICA to prevent ischemic damage.
Keywords: Cervical carotid artery dissection